Hengshun Aromatic Vinegar Ameliorates Vascular Endothelial Injury via Regulating PKCζ-Mediated Oxidative Stress and Apoptosis - Li, Xin; Gao, Meng; Zhu, Shenghu; Yin, Lianhong; Zhang, Bao; Qi, Yan; Zhao, Yanyan; Yu, Yongjian; Xu, Lina (Frontiers in Nutrition, 2021)
Vascular endothelial injury (VEI) is an early event of atherosclerosis, and reversing endothelial dysfunction has become a new trend in the prevention and treatment of cardiovascular diseases. Hengshun aromatic vinegar (HSAV), a traditional vinegar, has been reported to have many pharmacological activities, but its effect against VEI and the molecular mechanism are still unknown. In this study, effects of HSAV on VEI were evaluated in H2O2 induced human umbilical vein endothelial cells (HUVECs) and methionine induced VEI in rats. Results showed that HSAV significantly increased cell viability, inhibited apoptosis and reduced the generation of reactive oxygen species (ROS) in H2O2-induced HUVECs. Meanwhile, HSAV decreased serum homocysteine (Hcy), endothelin 1 (ET-1) and oxidized low density lipoprotein (ox-LDL) levels, increased nitric oxide (NO) and endothelin nitric oxide synthase (eNOS) levels, ameliorated pathological changes in rats with VEI induced by methionine. In parallel, HSAV relieved oxidative stress by decreasing malondialdehyde (MDA) level and increasing superoxide dismutase (SOD), glutathione (GSH) and glutathione peroxidase (GSH-Px) levels in rats with VEI. Mechanism studies indicated that HSAV markedly downregulated the expression of protein kinase C zeta (PKCζ), and consequently regulated sirtuin 1 (Sirt1) mediated oxidative stress signal pathway, and protein inhibitor of activated STATy (PIASy) mediated apoptosis pathway, leading to the alleviation of oxidative stress and inhibition of apoptosis. These regulative effects of HSAV were further validated by knochdown and overexpression of PKCζ in vitro. In conclusion, HSAV showed protective effect against VEI by inhibiting PKCζ, and thereby ameliorating oxidative stress and inhibiting apoptosis. This study not only provides guidance for the consumption of vinegar in daily life but also promotes the development of diet supplement for disease prevention.